Pengembangan Media Lift The Flap Book Materi Pembagian untuk Meningkatkan Minat dan Keaktifan Belajar Siswa Kelas 2 di SDN Sidodadi 1 Garum - Kholfatur Rofi'ah; Fathul Niam; Aang Yudho Prastowo (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2022)
This study aims to: produce a valid and effective lift the flap book to increase students' interest in learning mathematics. Initial data was collected only through classroom teacher interviews due to the Covid-19 fpandemic. fThe fresults fof fthe fpreliminary fstudy fare fused fas fthe fbasis ffor fmedia fdevelopment. fFurthermore, fdata fwere fcollected fby fobservation, fquestionnaires fand fdocumentation. fData fanalysis fused fquestionnaires fand fexpert fjudgment fsheets. fThe fresults fshowed fthat: f1) fthe fmedia fhas fmet fthe fvalidity fcriteria fbased fon fthe fresults fof fmaterial fvalidation fwith fa fpercentage fscore fof f90% fwhich fis fincluded fin fthe f